Regularidade e estimativas geométricas para mínimos de funcionais descontínuos e singulares - Leitão Júnior, Raimundo Alves (2012)
This work consists of two parts. In the first part we study nonnegative minimizers of general degenerate elliptic functionals, ∫ F (X, u, ∇u)dX → min, for variational kernels F that are discontinuous in ụ with discontinuity of order ~ X{u>0}. The Euler-Lagrange equation is therefore governed by a non-homogeneous, degenerate elliptic equation with free boundary between the positive and the zero phases of the minimizer. We show optimal gradient estimate and nondegeneracy of minima. We also address weak and strong regularity properties of free boundary, ∂ red {u>0}, has H n-1- total measure. For more specific problems that arise in jet flows, we show the reduced free boundary is locally the graph of a C1,y function. In the second part of work we provide a rather complete description of the sharp regularity theory for a family of heterogeneous, two-phase variational free boundary problems, y→ min, ruled by nonlinear, degenerate elliptic operators. Included in such family are heterogeneous jets and cavities problems of Prandtl-Batchelor type, y = 0; singular degenerate elliptic equations and obstacle type systems, y = 1. Linear versions of these problems have been subjects of intense research for the past four decades or so. The nonlinear counterparts treated in this present work introduce substantial new difficulties since the most of the classical theories developed earlier, such that as monotonicity and almost monotonicity formulae, are no longer available. Nonetheless, the innovative solutions designed in this work provide new answers even in the classical context of linear, nondegenerate equations.